2009
DOI: 10.1111/j.1471-0528.2008.02067.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Weighing up and balancing out’: a meta‐synthesis of barriers to antenatal care for marginalised women in high‐income countries

Abstract: Background In high-resource settings around 20% of maternal deaths are attributed to women who fail to receive adequate antenatal care. Epidemiological evidence suggests many of these women belong to marginalised groups often living in areas of relative deprivation. Reasons for inadequate antenatal attendance have yet to be fully evaluated.Objectives To identify the factors affecting access to antenatal care for marginalised pregnant women living in developed countries.Search strategy We included qualitative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
181
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(197 citation statements)
references
References 40 publications
12
181
2
2
Order By: Relevance
“…Where mothers lack mental capacity, misuse substances or are homeless, they may struggle to exercise informed reproductive choice leading to unplanned pregnancies (D' Souza and Garcia, 2004;Hepburn, 2004;Downe, et al, 2008). That teenagers are at greater risk of unplanned pregnancy is also a very well established finding (Ryan et al, 2008;Harden et al, 2009).…”
Section: New Initiatives: Embracing Continuity Of Carementioning
confidence: 99%
“…Where mothers lack mental capacity, misuse substances or are homeless, they may struggle to exercise informed reproductive choice leading to unplanned pregnancies (D' Souza and Garcia, 2004;Hepburn, 2004;Downe, et al, 2008). That teenagers are at greater risk of unplanned pregnancy is also a very well established finding (Ryan et al, 2008;Harden et al, 2009).…”
Section: New Initiatives: Embracing Continuity Of Carementioning
confidence: 99%
“…For example, the meta-synthesis of qualitative work by Downe et al 154 on antenatal care uptake identified several shared perceptions among marginalised groups relating to quality of care, the trustworthiness and cultural sensitivity of staff and feelings of mutual respect that shaped attendance. Similarly, Manderson and Allotey 155 report of the 'story-telling' about health services that takes place within immigrant communities in Australia and shapes their uptake of health care.…”
Section: Norms Attitudes and Understandings Regarding The (Dis)benefmentioning
confidence: 99%
“…Minority or marginalized women in a high-income country do not appear to display a "healthism" approach to their lives [50]; normative assumptions in antenatal guidelines do not apply. This may be in part due to a lack of trust in caregivers among minority women in Western countries [50,51], the authoritative source often are their husband [51] or their mother [52], instead of the health care services. While printed educational materials are widely used to improve knowledge, awareness and attitudes, especially in developed countries, other methods for information Table 5 and education may be needed for cultural minority groups.…”
Section: Mothers Of Non-western Origin -Less Access To Informationmentioning
confidence: 99%
“…Two of these trials were conducted in total populations (114;119), while two were conducted in mixed low-and high-risk populations within single institutions (116-118). Three studies (Neldam 1983 (50) and the study by Lobb and coworkers in 1985 (116) were both conducted in mixed low-and high-risk populations within single institutions. Even though the study by Neldam is the only randomized controlled trial (RCT) to date of antepartum testing of any kind versus no testing that has found reduced mortality, it has been found by some researchers to be methodologically substandard since the randomization procedure was based on the mother's initial even or odd booking number when included in the study (57).…”
Section: Effects Of Increased Maternal Awareness Toward Fm In Populatmentioning
confidence: 99%